2014
DOI: 10.1371/journal.pone.0099494
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Vesicles Deliver Cdc42p to Sites of Polarized Growth in S. cerevisiae

Abstract: The activation and localization of the Rho-family GTPase Cdc42p at one pole of a cell is necessary for maintaining an axis of polarized growth in many animal and fungal cells. How the asymmetric distribution of this key regulator of polarized morphogenesis is maintained is not fully understood, though divergent models have emerged from a congruence of multiple studies, including one that posits a role for polarized secretion. Here we show with S. cerevisiae that Cdc42p associates with secretory vesicles in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This suggests that either there is some active mechanism for increasing the concentration of signaling molecules in the membrane following vesicle fusion, or some other factor is transported by vesicles that maintains cell polarization. Interestingly, experimental evidence for the former mechanism has recently been obtained by establishing that vesicles deliver Cdc42 to sites of polarized growth in yeast [9]. In this paper, we relax both assumptions (i) and (ii) and show that a more biophysically realistic model of active vesicular transport in the cytoplasm leads to an advection-diffusion equation with anisotropic and space-dependent diffusion.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…This suggests that either there is some active mechanism for increasing the concentration of signaling molecules in the membrane following vesicle fusion, or some other factor is transported by vesicles that maintains cell polarization. Interestingly, experimental evidence for the former mechanism has recently been obtained by establishing that vesicles deliver Cdc42 to sites of polarized growth in yeast [9]. In this paper, we relax both assumptions (i) and (ii) and show that a more biophysically realistic model of active vesicular transport in the cytoplasm leads to an advection-diffusion equation with anisotropic and space-dependent diffusion.…”
Section: Introductionmentioning
confidence: 77%
“…A dynamic equilibrium of recycling can be maintained only if endocytic vesicles also have an enhanced concentration of signaling molecules. There are various active mechanisms for enhancing the concentration of proteins within vesicles, and although evidence for such processes within the context of cell polarization is currently lacking, it has recently been observed that vesicles do indeed deliver Cdc42 to sites of polarized growth in yeast [9]. We will ignore these issues here and simply assume that each vesicle contains n ves signaling molecules and the membrane concentration increases/decreases by an amount γn ves given a unit flux of vesicles undergoing exo/endocytosis.…”
Section: Deterministic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It, thus, seems that Cdc42 activated at the Golgi membranes downstream of GM130 replenishes the PM pool of active Cdc42 required for directional cell migration and maintenance of cell polarity. Indeed, in fission yeast, active Cdc42 is present on secretory vesicles and delivered to sites of polarized growth [80]. Likewise, in mammalian cells, Cdc42 has been detected on Arf6-positive intracellular vesicles, which are trafficked en route to the leading edge of migration cells [55].…”
Section: Rho Gtpases Acting Along the Secretory Pathwaymentioning
confidence: 99%
“…Additionally, the specific requirement for Osh protein function in polarized exocytosis could be that it facilitates Cdc42p localization at the bud tip of small and medium sized buds (Kozminski et al, 2006;Dighe and Kozminski 2014). Cdc42p…”
Section: Is Sterol or Ps Transfer By Orps Essential?mentioning
confidence: 99%